Screen Time and Mental Health Among Adolescents - Mougharbel, Fatima (Université d'Ottawa / University of Ottawa, 2023)
Adolescence is a period of dynamic behavioural and emotional development that can increase young people's vulnerability to mental health problems. With 70% of mental disorders having their onset during childhood or adolescence, identifying modifiable factors of these disorders among adolescents can help inform future interventions aiming to improve mental health. One of these factors is electronic technology which has become pervasive in our modern society, occupying an important portion of young people's days and changing their lifestyle. This has created serious concerns regarding the impact of heavy recreational screen use on adolescents' health, especially with the vast majority exceeding the sedentary recreational screen time recommendations of 2 hours or less per day. Evidence suggests that screen time can be associated with adolescent mental health problems. However, little is known about how the extent, nature, and types of recreational screen engagement among adolescents are associated with mental health problems as the body of evidence is very mixed, and many questions remain unanswered. Accordingly, the aims of this dissertation were: i) to summarize the evidence regarding correlates of sedentary screen pursuits among youth, ii) to examine how different types of screens, incorporating their newer forms, are associated with adolescents' mental health cross-sectionally and longitudinally, iii) to examine the nature of screen use and its association with suicidal behaviours; and iv) to explore the moderating role of sex, age, and parental support in the association between screen time and different mental health problems. To achieve these objectives, we completed four manuscripts, all prepared for submission to peer-reviewed scientific journals: 1. A narrative review on the psychological correlates of sedentary screen time behaviour among children and adolescents. 2. Heavy social media use and psychological distress among adolescents: the moderating role of sex, age, and parental support. 3. Problematic technology use, suicidal ideation, and suicide attempt among adolescents: the moderating role of sex. 4. Longitudinal associations between different types of screen use and depression and anxiety symptoms in adolescents. Collectively, our results identified that high levels of sedentary screen behaviour are associated with more severe anxiety, depressive symptoms, and suicidality among adolescents. However, the strength of associations varied between some screen types. Additionally, the findings of this dissertation indicate that a further increase in screen time is associated with increased mental health problems. Lastly, an important role of sex and age in this association was identified. These results can be used to inform future research in this field and guide future interventions designed to manage screen use among adolescents and improve their mental health.
Keywords: Mental Health; Screen Time; Adolescents